2020
DOI: 10.1001/jamanetworkopen.2020.1262
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Electronic Health Record–Based Suicide Risk Prediction Modeling Approach Across Multiple Health Care Systems

Abstract: IMPORTANCE Suicide is a leading cause of mortality, with suicide-related deaths increasing in recent years. Automated methods for individualized risk prediction have great potential to address this growing public health threat. To facilitate their adoption, they must first be validated across diverse health care settings.OBJECTIVE To evaluate the generalizability and cross-site performance of a risk prediction method using readily available structured data from electronic health records in predicting incident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 27 publications
1
66
0
Order By: Relevance
“…With the present study, we extend a previous line of research on predictive modeling based on EHR data. While previous studies have demonstrated empirical evidence for the predictive validity of EHR data in psychiatric use cases [18][19][20], to the best of our knowledge the present study is the first to not only report on the design but also on successful implementation and technical feasibility of the informatics infrastructure for standardized acquisition, transfer, storage and access of real world data for analytic purposes in psychiatric care which is the basic requirement for the application and validation of predictive models in future clinical studies.…”
Section: Results In Relation To Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the present study, we extend a previous line of research on predictive modeling based on EHR data. While previous studies have demonstrated empirical evidence for the predictive validity of EHR data in psychiatric use cases [18][19][20], to the best of our knowledge the present study is the first to not only report on the design but also on successful implementation and technical feasibility of the informatics infrastructure for standardized acquisition, transfer, storage and access of real world data for analytic purposes in psychiatric care which is the basic requirement for the application and validation of predictive models in future clinical studies.…”
Section: Results In Relation To Other Studiesmentioning
confidence: 99%
“…Hence, ecologically valid predictive models would require access to standardized real world data collected at the point-of-care [17]. Importantly, large-scale studies reporting the successful application of multivariate models trained on data from Electronic Health Record (EHR) including features such as diagnosis and procedures, laboratory parameters and medication for the prediction of suicide risk or weight gain following antidepressant treatment have demonstrated the capacity and generalizability of predictive models trained on real-world data [18][19][20]. Further extension of EHRs via standardized collection of predictive variables such as known risk factors might further enhance the potential of this novel data entity for predictive analytics in psychiatry [21,22].…”
Section: Introduction 11 Scientific Backgroundmentioning
confidence: 99%
“…Instead, the IAT could be used in conjunction with additional metrics with good psychometric properties to more comprehensively evaluate risk. For instance, advances in machine learning techniques could be used to help identify the most at‐risk individuals (e.g., Barak‐Corren et al., 2020; Ribeiro, Huang, Fox, Walsh, & Linthicum, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The time-variant changes in these factors make the task of diagnosis for MHPs more challenging [ 15 ]. Even though Electronic Health Records (EHRs) are longitudinal, studies have predominantly relied on time-invariant modeling of content to predict suicide-related ideations, suicide-related behaviors, and suicide attempt [ 16 , 17 ]. This approach is often employed due to patients’ low engagement and poor treatment adherence resulting ill-informed follow-up diagnostic procedure.…”
Section: Introductionmentioning
confidence: 99%